Thermal and thermodynamic properties of duplex DNA containing site-specific interstrand cross-link of antitumor cisplatin or its clinically ineffective trans isomer - Hofr, C; Brabec, V (The Journal of biological chemistry, 2001)
The effect of the single, site-specific interstrand cross-link formed by cisplatin or transplatin on the thermal stability and energetics of a 20-base pair DNA duplex is reported. The cross-linked or unplatinated 20-base pair duplexes were investigated with the aid of differential scanning calorimetry, temperature-dependent UV absorption, and circular dichroism. The cross-link of both platinum isomers increases the thermal stability of the modified duplexes by changing the molecularity of denaturation. The structural perturbation resulting from the interstrand cross-link of cisplatin increases entropy of the duplex and in this way entropically stabilizes the duplex. This entropic cross-link-induced stabilization of the duplex is partially but not completely compensated by the enthalpic destabilization of the duplex. The net result of these enthalpic and entropic effects is that the structural perturbation resulting from the formation of the interstrand cross-link by cisplatin induces a decrease in duplex thermodynamic stability, with this destabilization being enthalpic in origin. By contrast, the interstrand cross-link of transplatin is enthalpically almost neutral with the cross-link-induced destabilization entirely entropic in origin. These differences are consistent with distinct conformational distortions induced by the interstrand cross-links of the two isomers. Importantly, for the duplex cross-linked by cisplatin relative to that cross-linked by transplatin, the compensating enthalpic and entropic effects almost completely offset the difference in cross-link-induced energetic destabilization. It has been proposed that the results of the present work further support the view that the impact of the interstrand cross-links of cisplatin and transplatin on DNA is different for each and might also be associated with the distinctly different antitumor effects of these platinum compounds.
Keywords: teplota; Calorimetry, Differential Scanning; entropie; Stereoisomerism; Molecular Sequence Data; reagencia zkříženě vázaná; cisplatina; stereoizomerie; Cisplatin; Antineoplastic Agents; termodynamika; chemické modely; ultrafialové záření; protinádorové látky; Cross-Linking Reagents; Entropy; sekvence nukleotidů; Nucleic Acid Conformation; molekulární sekvence - údaje; cirkulární dichroismus; DNA; diferenciální skenovací kalorimetrie; Ultraviolet Rays; Spectrophotometry; spektrofotometrie; Thermodynamics; Circular Dichroism; konformace nukleové kyseliny; Base Sequence; Temperature; Models, Chemical